PENGEMBANGAN BAHAN AJAR ENGLISH-TEXTUAL-GENRE BERBASIS ANDROID DALAM IMPLEMENTASI PPK KURIKULUM 2013 EDISI REVISI - Didit Kurniadi; Mohamad Fajarianditya Nugroho (Universitas Aki, 2020)
The implementation of the revised edition of the Curriculum of 2013 in Indonesia for millennial generation students does not focus on increasing the competency of the subjects only, but rather on improving the character, especially independence. This research is based on the issue of whether there is a significant relationship between teaching materials based on ETG (Educational Technology Gadget) on improving the competence of students' IBC and English as well as differences in student achievement in English subjects taught on an ETG basis when compared with non-ETG. The objectives to be achieved in this study are to investigate and examine whether there is a significant relationship between ETG-based teaching materials on improving the competence of IBC and English students and to find out whether there are differences in student achievement in English subjects taught with ETG-based if compared to non ETG ones. The research method is R&D with a type of factorial design research sourced from quantitative experiments. Beyond literature studies, curriculum analysis, and surveys, research starts from pre-test, treatment, post-test, data collection and analysis which are then concluded as indicators of performance. Keywords: Character, Millenial Generation, IBC, English, ETG